Navigating Uncertainty: The Role of Gold, Silver, Oil, Cryptocurrency, and ESG indices in the MENA Region - Sakr, Rahaf Zakaria (AUC Knowledge Fountain, 2023)
This study examines the effectiveness of various financial instruments as hedges and safe havens during different market conditions in the MENA region. It compares traditional safe-haven investments ( gold, silver, and oil) and non-traditional safe-havens (cryptocurrencies and ESG stocks) to determine which investments function better as hedges and safe havens during different market conditions. The data covers eight years, starting in 2015 and ending in early 2023. DCC GARCH is utilized to examine time variation in conditional correlations. This study finds that Gold, Silver, and cryptocurrency can be considered strong hedges to the MENA market on average and weak safe havens during times of uncertainty. Oil can only be considered a weak hedge on average and presents stable correlations with the MENA index during specific periods. The ESG index does not provide evidence for being a good hedge or safe-haven.